The use of in situ simulation to detect latent safety threats in paediatrics: a cross-sectional survey. (3rd November 2015) - Auerbach, Marc; Kessler, David O; Patterson, Mary
Abstract : Background: In situ simulation (ISS) has been reported as an innovative method to identify and mitigate latent safety threats (LSTs) in healthcare. Little is known about the current utilisation of ISS across academic simulation programmes. Objective: This study aims to describe the use of ISS to identify LST across paediatric academic simulation programmes. Methods: A 25-question cross-sectional survey was conducted at two simulation meetings in January 2014 to recruit leaders from paediatric simulation programmes. The total eligible sample was 82 individuals representing 48 distinct academic medical centres. The 25 survey questions were created to describe the constructs of: (1) utilisation of ISS (location, participants, cancellations and coordination) and (2) the outcomes of ISS (detection of and response to safety threats). Descriptive statistics were carried out using SPSS V.21.0 (IBM Corp released 2012). Results: The response rate was 68% (56/82), representing 79% (38/48) of the eligible academic medical centres. The majority of respondents (52/56) reported that their programmes utilised ISS. ISS was most commonly conducted in acute care settings. Almost all respondents (48/52) detected an LST during ISS. More than half of the respondents (28/52) utilised a formal reporting process after ISS sessions to feedback the LST to other individuals within their institution. 23% (12/52) of respondents reported the detection of a serious LST in ISS that was not resolved and subsequently led to a safety event during real patient care. Conclusions: The use of ISS to identify and mitigate LST is common in this cross-sectional survey of paediatric simulation programmes. Diverse processes and organisational structures exist for reporting and mitigating LSTs identified in ISS. A more integrated and systematic approach to ISS and LST could help ensure the mitigation of LSTs before they impact on patients.